Islamic Inheritance Systematics in The City of Binjai (Case Study Of The Division Of Inheritance Of Daughter And Biological Uncle) - Adliya Muchni Muharrama; Hasan Matsum; Muhammad Syukri Albani Nasution (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2020)
The problem of inheritance that is often a problem in society is when a dead leaves only daughters so that the father's brother gets the inheritance because there are no barriers to inheritance. In general, the dead's wife and daughter are not willing to leave the inherited properties due to the roles of the father's biological brother as long as the dead ( father ) does not play a maximum role as guardian. However, if the biological uncle's share is not given, it is feared that there will b damage to the family relationships between the biological uncle and the dead daughter. So later, in Binjai City, the biological uncle was still given the inheritance, but only part of the actual portions. This study analyzes the practice of inheritance settlement between uncles and daughters in the Binjai City community and the legal arguments of religious leaders who play a role in it. The research method used is field-qualitative with a normative approach and legal sociology. This research found that in solving the distribution of inheritance between daughters when dealing with paternal brothers in Binjai City, there are generally two ways of settlement, namely: First, the clergy want to remain consistent in applying the provisions of inheritance law by traditional fiqh, namely the father's biological brother gets the share of the heir when dealing with an only daughter. Second, scholars try to update the meaning of Islamic inheritance law by placing the position that a daughter can wear the hijab from her father's brother.